Passivation behavior of 316L stainless steel in artificial seawater: effects of pH and dissolved oxygen. Issue 2 (28th April 2021) - Wang, Zhaopeng; Wang, Yi; Zhang, Bowei; Zhang, Zhan; Xiao, Kui; Wu, Junsheng; Yao, Qiong; Ma, Guojia; Sun, Gang
Abstract : Purpose: The purpose of this paper is to investigate the influence of the potential of hydrogen (pH) and dissolved oxygen in artificial seawater on the passivation behavior of 316L stainless steel. Design/methodology/approach: The corrosion behavior was studied by using electrochemical measurements such as electrochemical impedance spectroscopy and polarization curve. The passive films were characterized with X-ray photoelectron spectroscopy. Findings: The polarization resistance of the passive film decreases as the pH value drops ascribed to the formation of much more point defects. The donor carrier concentration (ND) in the passive film formed in the deaerated condition is lower than that in aerated conditions. Nevertheless, this phenomenon is the opposite when the pH value is 1 due to the significant decrease of Fe oxides/hydroxides coupled with the stable content of Cr oxides/hydroxides species. In addition, the compositional variation of the passive film also leads to the changes of its semiconductor properties from N-type to bipolar type. Originality/value: This paper shows the variation of polarization resistance, corrosion potential, passive film composition and semiconductor properties with the pH value and dissolved oxygen. The results can serve as references to the further study on crevice corrosion of 316L in seawater.